Preserving the monarchy : the comte de Vergennes, 1774-1787 - Price, Munro (Cambridge University Press, 1995)
The comte de Vergennes is best known as one of the great foreign ministers of modern French history, but for much of the 1780s he was also first minister in all but name. This 1995 book was the first to deal in depth with the critical part he played in French domestic policies on the eve of the Revolution. It studies Vergennes' role in the context of the debate on the nature and future of the French monarchy in the two decades before the Revolution. His financial reforms, fully examined here, were the last attempt to restructure the monarchy in accordance with its traditional principles. The failure of this undertaking accelerated the final collapse of the royal government. Preserving the Monarchy is based on archival research, as well as reinterpretations of the established sources. The result is a significant study, not merely of Vergennes but of the end of the ancien régime.